2022
DOI: 10.4314/tjpr.v21i6.7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of β-eudesmol against septic liver injury via inhibition of NF-κB signaling

Abstract: Purpose: To investigate the role of β-eudesmol in septic liver injury in mice.Methods: Mice were intraperitoneally injected with 50 or 100 mg/kg β-eudesmol, and then subjected to cecal ligation and puncture for the establishment of a septic model 2 h later. Haematoxylin and eosin staining was used to evaluate histopathological changes in the liver tissues. Terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) staining and enzyme-linked immunosorbent assay (ELISA) were employed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Consistently, SSa inhibits NLRP3 inflammasome and autophagy via AMPK/mTOR pathway, which induces the inactivation of pancreatic stellate cells, thereby improving pancreatic fibrosis [16]. Saikosaponin D can also suppress NLRP3 inflammasome activation to relieve liver fibrosis [10,18]. The present study showed that SSa diminished the CCl4-induced relative levels of markers of the NLRP3 inflammasome in liver tissues, indicating that SSa suppressed CCl4-induced activation of the NLRP3 inflammasome.…”
Section: Ssa Repressed Ccl4-induced Expression Of Hedgehog Signaling ...supporting
confidence: 73%
See 1 more Smart Citation
“…Consistently, SSa inhibits NLRP3 inflammasome and autophagy via AMPK/mTOR pathway, which induces the inactivation of pancreatic stellate cells, thereby improving pancreatic fibrosis [16]. Saikosaponin D can also suppress NLRP3 inflammasome activation to relieve liver fibrosis [10,18]. The present study showed that SSa diminished the CCl4-induced relative levels of markers of the NLRP3 inflammasome in liver tissues, indicating that SSa suppressed CCl4-induced activation of the NLRP3 inflammasome.…”
Section: Ssa Repressed Ccl4-induced Expression Of Hedgehog Signaling ...supporting
confidence: 73%
“…In addition, SSa and/or curcumin attenuate hepatic inflammation and fibrosis in carbon tetrachloride (CCl4)-treated rats [8]. Furthermore, saikosaponin D (SSd) alleviates liver fibrosis by regulating autophagy and the NLRP3 inflammasome [9,10]. However, the effect and mechanism of SSa on liver fibrosis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, retardation of the activation of NF-κB suppresses the generation of inflammatory cytokines and liver injury [19]. The NF-κB pathway has been revealed as playing a role in the progression of sepsis [8][9][10]; however, whether PCA1 modulates NF-κB pathway thereby ameliorating sepsis remains unknown. In this study, the protein levels of p-p65/p65 and p-IκBα increased, and that of IκBα decreased after LPS treatment, but these changes were reversed by PCA1 treatment, indicating that PCA1 inhibited NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB pathway has been shown to participate in the progression of sepsis [8][9][10]. However, whether PCA1 modulates the NF-κB pathway to attenuate sepsis progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%